E-051 Racial and socioeconomic disparities in intracranial hemorrhage outcomes: analysis from the nationwide inpatient sample. (23rd July 2022) - Siddiqui, N; Hardigan, T; De Leacy, R; Majidi, S
Abstract : Introduction: Primary intracranial hemorrhage (ICH) is a significant cause of morbidity and mortality. We sought to determine the impact of race and socioeconomic status on the clinical outcome. Methods: Nationwide Inpatient Sample from 2006 to 2015 were reviewed to identify patients with primary diagnosis of primary ICH with ICD-9 (431.XX). Baseline characteristics, and disease severity were compared between patients with good outcome and those with poor outcome or in-hospital mortality. Good outcome was defined as discharge to home or acute rehabilitation facility. Propensity score matching was utilized to control for significantly different potential baseline confounders. Following grouping by race and demographic characteristics, outcomes were compared with respect to all-cause mortality, discharge disposition, length of stay, and hospitalization costs. T-tests (numerical variables) and chi-squared (categorical) or their nonparametric alternatives were utilized to compare outcomes, as appropriate. Odds ratios were calculated for each respective predictor. Statistical significance was set p<0.05. Results: A total of 16497 cases met inclusion/exclusion criteria, representing a total of 82087 patients with ICH from years 2006 to 2015. Mean age was 57.6 (sd 17.7), with 45.8% patients being female. Of the patients presenting, 63.8% were White, 15.2% Black, 11.2% Hispanic/Latino, 4.7% Asian, 0.6% Native American, and 4.5% Other. Most patients had Medicare (39.7%) or private insurance (35.2%) as the primary insurance, with 15.5% on Medicaid. Racial Breakdown: After controlling for baseline characteristics via propensity matched analysis, Black patients had higher rates of inpatient mortality than White (odds ratio [OR] 1.25; confidence interval CI: [1.12, 1.39]). Hispanic/Latino [OR 1.07; CI [0.94, 1.22]), Asian OR 0.99, CI [0.81, 1.20]), Native American (OR 1.09, CI [0.63, 1.79]), and Other (OR 1.05, CI [0.86, 1.27]) did not have significantly different odds of mortality. Black patients were slightly less likely to receive a craniotomy (OR .95, CI [0.91, 0.99]) than White, while all other racial groups were more likely to receive a craniotomy than White. Hispanic/Latin had the highest mean charge (139284 sd 217618), followed by Asian (132645, sd 198542), and Other (121742 sd 191789); (p<0.01). White patients had the shortest length of hospitalization (mean 8.1 days, p<0.0001), an effect which reversed after propensity matching for age and comorbidities. Insurance Breakdown: Patients on Medicaid had the highest mean cost (162607 sd 256707) and were likely to stay the longest (mean 16.1 days sd 24.6), followed by patients who were privately insured (113738 sd 181902). There was no significant difference in odds of mortality for any insurance except self pay/other (OR 1.21; CI: [1.13, 1.29], as comparted to Medicare) based on insurance when controlling for disease severity and comorbidities. Medicare patients were the least likely to receive craniotomy (p<0.01). There was a significantly lower discharge to home for Medicare vs non-Medicare patients (p<0.01). Conclusions: This analysis of nationally representative database demonstrates racial and socioeconomic disparity in the outcome of primary ICH independent to the disease severity. African-Americans, Hispanics, and patients with low household income tend to have poor hospital outcome. Further studies warranted to understand the impact of race and socioeconomic status on the clinical outcome of primary ICH. Disclosures: N. Siddiqui: None. T. Hardigan: None. R. De Leacy: None. S. Majidi: None.